Le jardin japonais d’Aix-en-Provence : une conception hybride entre Japon et Méditerranée - Benoît Romeyer; Jean-Noël Consalès (Projets de Paysage)
While the international presence of the Japanese garden bears witness to the dissemination of models in landscape architecture, it also raises the question of the diversity of its territorial variations. This article looks at the forms taken by this characteristic style of garden in a Mediterranean context. The harshness of the Mediterranean climate makes it difficult to simply copy Japanese garden designs. The question then is whether the Japanese garden is a global model capable of being hybridised with other cultural elements and garden arts. The recently created Japanese garden in Aix-en-Provence, inaugurated in 2021, is the fruit of the influences of Japanese design and the Mediterranean context while combining French and Japanese gardening knowledge and know-how. It would appear to be a good case study to investigate this question. The aim of this article is to analyse the forms of hybridisation that this garden embodies from three perspectives: its design, its spatial composition and the way it is received by its users.